Comprehensive biodiversity assessment of flora and fauna along the Kedah coastline: Implications for conservation and sustainable management - Ebrahim Al-Qadami; Mohd Adib Mohammad Razi; Mohamad Fahmi Mohamad Ideris; Mahran Mahamud; Syed Muzzamil Hussain Shah; Jaan H. Pu; Mugahed Amran; Siva Avudaiappan; Alberto González Figueroa (Results in Engineering)
Preserving the unique ecosystems of specific coastal areas is crucial for environmental health and the welfare of local communities. This study explores the rich biodiversity of flora and fauna along the Kedah state coastline, a 440 km stretch along the Strait of Malacca. Through meticulous site surveys and comprehensive data collection across multiple locations, followed by laboratory analyses, this research reveals a vibrant tapestry of life. The Kedah coastal area boasts a remarkable diversity, with 60 fish species identified, predominantly from the Carangidae (12 %) and Mugilidae (10 %) families. Additionally, five marine mammal species were documented, though turtles and terrapins were notably absent. The condition of coral reefs varied, with ''fair'' conditions observed at stations St-1 and St-2 (31.67 % and 35.67 % live coral, respectively), and ''poor'' conditions at St-3 (10.67 % live coral). High densities of phytoplankton, zooplankton, macrobenthos, and seaweed were recorded, whereas seagrass vegetation was absent. The study on Kedah’s coastal flora and fauna revealed a diverse range of species, including fish, marine mammals, corals, phytoplankton, zooplankton, macrobenthos, and seaweed. Coral reefs were found to be in varying conditions, with some needing restoration. The study recommends long-term monitoring, seasonal surveys, and focused research on key species. Habitat protection, community awareness, and sustainable practices are also emphasized to preserve the ecological balance of these marine environments. Moreover, the findings of this study provide a critical understanding of the Kedah coastal ecosystem and offer valuable insights for local authorities to develop effective conservation strategies. This research underscores the importance of preserving biodiversity to maintain ecological balance and support sustainable development in coastal regions.